Density control by pellets in plasmas with ELM mitigation by RMPs in the ASDEX Upgrade tokamak. (27th June 2018) - Valovič, M; Lang, P T; Kirk, A; Suttrop, W; Cavedon, M; Dunne, M; Fischer, R; Garzotti, L; Guimarais, L; Leuthold, N; Mc Carthy, P J; Meyer, H; et al.
Abstract: This paper describes the extension of the previous experimental database on density control by pellets and ELM control by RMPs in the ASDEX Upgrade tokamak. A stationary low triangularity plasma is sustained by simultaneous pellet fuelling and RMP ELM control at ion pedestal collisionality of ν * i, ped ∼ 0.5. Refuelling of the RMP induced density pump-out requires a pellet rate of Φpel ∼ 0.073 P aux / T t, ped . The duration of refuelling of density pump-out can be minimised to about 3 energy confinement times. Pellet fuelling increases or preserves ion pedestal pressure with respect to unfuelled ELM suppressed/mitigated phase. Pellets cause transition from ELM suppression to ELMy regime: At low triangularity, the first pellet triggers a transition to an ELMy phase but subsequent ELMs are not modulated by pellets. At elevated triangularity, initial pellets trigger ELM-like events but in-between pellets ELM suppression is preserved. In later phase, as density increases the plasma transitions to an ELMy phase similar to low triangularity case.